Sleeping Beauty gets assertive: a short-term group for students who lack assertiveness skills is sufficient to kickstart a new mindset. - Cooper J (Therapy Today, 2007)
A short-term group for students who lack assertiveness skills is sufficient to kickstart a new mindset.